Recent progress of life science technology in Japan - Ikawa, Yoji, 1934-; Wada, Akiyoshi (Academic Press, 1989)
Recent Progress of Life Science Technology in Japan discusses developments in cancer research technologies in Japan. In June 1983 an intra-cabinet panel of the Japanese Government drafted a 10-year strategy for cancer control, recognizing the importance of this field of research. A scientific research group was organized to comprise two sections-the first concerning the development and evaluation of DNA technologies, and the second on protein-related technologies.